PENGARUH MANFAAT DAN KEBERHASILAN USAHATERNAK DOMBA (Ovis aries) TERHADAP KEBERLANJUTAN KERJASAMA KEMITRAAN: (Kasus Terhadap Peternak Domba Kerjasama Kemitraan Dengan CV. Kurma Adzwa Farm di Provinsi Jawa Barat) - Jaenudin (OrchidAgri, 2025)
JAENUDIN, 2024. The Effect of the Benefits of Partnership Cooperation and the Success of Sheep Farming on the Sustainability of Partnership Cooperation (Case of Sheep Farmers in Partnership Cooperation with CV. Kurma Adzwa Farm in West Java Province). Under the guidance of Euis Dasipah and Nataliningsih. This study aims to determine the effect of the Benefits of Partnership Cooperation and the Success of Sheep Farming Business on the Sustainability of Partnership Cooperation. The unit of analysis is sheep farmers who partner with CV. Kurma Adzwa Farm in West Java Province. The technique of determining respondents was carried out by simple random sampling obtained by 70 people. Analysis techniques are used pearson correlation analysis and path analysis. The results of the study obtained the Demonstration of the Benefits of Partnership Cooperation in West Java Province which consisted of the following dimensions: Provision of production facilities; Technical guidance, and Marketing of Production Results obtained an achievement level of 80% good criteria. The Success of Sheep Farming in West Java Province which consists of the following dimensions: Product selling price; and Sheep Business Profit obtained an achievement rate of 79.64% good criteria. Demonstration of the Success of Sheep Farming in West Java Province which consists of the following dimensions: Product selling price; and Sheep Business Profit obtained an achievement rate of 79.64% good criteria. Demonstration of Sustainability of Sheep Business Partnership Cooperation in West Java Province which consists of the following dimensions: Economic Aspects; Social Aspect; and Ecological Aspects obtained an achievement level of 79.20% good criteria. There is a strong positive correlation between the Benefits of Partnership Cooperation and the Success of Sheep Farming in West Java Province which is shown by the correlation coefficient r = 0.692. The higher / greater the benefits of partnership cooperation, the better the success of the sheep farm. The Benefits of Partnership Cooperation and the Success of Sheep Farming Business have a positive effect on the Sustainability of Partnership Cooperation. The respective contributions were 15.01% and 60.32%. Keywords: Partnership, Success, Sustainability.